Walentyniańska interpretacja biblijnego opisu stworzenia człowieka (Rdz 1, 26-27) w przekazie Klemensa Aleksandryjskiego - Szczur, Piotr (Vox Patrum, 2018)
The article attempts to show the Valentinus’ interpretation of the Biblical description of the creation of man (Gen 1:26-27) in Excerpta ex Theodoto prepared by Clement of Alexandria. The first part of the article shows the character of Valentinus and his school; the second part shows the importance of Excerpta for getting to know the Valentinian heresy; the third part analyzes the fragments of Excerpta ex Theodoto referring to the Biblical description of man’s creation and to the anthropology proposed by Theodot – one of the representatives of the Eastern School.